In: Statistics and Probability
I
(a)
P(1/2
X
3/2) = F(3/2) - F(1/2)
= (1/2) * (3/2) - (1/2) * (1/2) {F(x) = x/2 for 0
x
2}
= (3/4) - (1/4)
= 1/2
(b)
P(1
X < 2) = F(2) - F(1)
= (1/2) * 2 - (1/2) * 1 {F(x) = x/2 for 0
x
2}
= 1 - (1/2)
= 1/2
(c)
Y
X
=> X2
X
=> X - X2
0
=> X (1 - X)
0
which is true if X
0 and X
1 (or 0
X
1)
or X
0 and X
1 (which is not possible at the same time.)
Thus,
P(Y
X ) = P(0
X
1) = F(1) - F(0)
= (1/2) * 1 - (1/2) * 0
= 1/2
d)
X
2Y
=> X
2X2
=> 2X2 - X
0
=> X (2X-1)
0
which is true if X
0 and X
1/2 (=> X
1/2)
or X
0 and X
1/2 (=> X
0)
Thus,
P(X
2Y ) = P(X
1/2) + P(X
0) = 1 - P(X
1/2) + 0 {F(X) = 0 for X < 0}
= 1 - F(1/2)
= 1 - (1/2) * (1/2)
= 1 - (1/4)
= 3/4
(e)
X + Y
3/4
=> X + X2
3/4
=> X2 + X - (3/4)
0
=> X2 + X - (3/4)
0
=> (X + 3/2) (X - 1/2)
0
which is true if X
-3/2 and X
1/2 (which is not possible at the same time.)
or X
-3/2 and X
1/2 (or -3/2
X
1/2)
Thus,
P(X + Y
3/4 ) = P(-3/2
X
1/2) = F(1/2) - F(-3/2)
= (1/2) * (1/2) - 0 {F(x) = 0 for X < 0 and F(x) = x/2 for 0
x
2)
= 1/4